2021
DOI: 10.1101/2021.03.26.21254383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased angiotensin-converting enzyme 2, sRAGE and immune activation, but lowered calcium and magnesium in COVID-19: association with chest CT abnormalities and lowered peripheral oxygen saturation

Abstract: Background. The characterization of new biomarkers of COVID-19 is extremely important. Few studies measured the soluble receptor for advanced glycation end product (sRAGE), angiotensin-converting enzyme 2 (ACE2), calcium and magnesium in COVID-19. Aims: To measure sRAGE, ACE2, interleukin (IL)-6, IL-10, CRP, calcium, magnesium, and albumin in COVID-19 patients in association with peripheral oxygen saturation (SpO2) and chest CT scan abnormalities (CCTA) including ground glass opacities. Methods. This study… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 120 publications
4
13
2
Order By: Relevance
“…In agreement with Al-Hakeim et al (2020) and other studies reviewed in the latter paper [31], this study found that serum albumin, and total calcium and magnesium were significantly lowered in COVID-19. Hypoalbuminemia may be explained by the acute phase responses in COVID-19 with increased breakdown of albumin and increased production of positive acute phase proteins [71], and by enhanced capillary permeability leading to the leaking of albumin to the interstitial space [72].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with Al-Hakeim et al (2020) and other studies reviewed in the latter paper [31], this study found that serum albumin, and total calcium and magnesium were significantly lowered in COVID-19. Hypoalbuminemia may be explained by the acute phase responses in COVID-19 with increased breakdown of albumin and increased production of positive acute phase proteins [71], and by enhanced capillary permeability leading to the leaking of albumin to the interstitial space [72].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, we published that chest CT abnormalities (CCTAs) (comprising ground-glass opacities (GGOs), pulmonary densification areas consistent with residual lesions, pneumonic consolidation, and crazy-paving patterns), could be observed in 78.3% of RT-PCR test–proven COVID-19 cases and that the presence of CCTAs was characterized by significantly lowered peripheral oxygen saturation (SpO2) and serum levels of albumin [31]. The latter is a negative acute phase protein which is lowered in response to the systemic inflammatory response in COVID□19 [1, 31-33]. Moreover, lowered SpO2 values were significantly associated with signs of immune activation, and positively with albumin, magnesium, and calcium [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chest imaging, especially computed tomography scan (CT-scan), is critical for the diagnosis, management, and follow-up of COVID-19 infection (Fang Y, 2020;Zhang et al, 2020a). CT scan anomalies (CCTAs), including ground-glass opacities (GGOs), pulmonary densification areas consistent with residual lesions, pneumonic consolidation, and crazy-paving trends are observed in 78.3% of RT-PCR test-proven COVID-19 patients and are associated with lower peripheral oxygen saturation (SpO2) (Al-Hakeim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 and increased CCTAs are accompanied by increased serum IL-6, CRP, and IL-10, and lowered albumin and oxygen saturation percentage (SpO2) . Moreover, we detected increased levels of sRAGE (soluble receptor for advanced glycation end-products) and angiotensin converting enzyme 2 (ACE2) in COVID-19 patients (Al-Hakeim et al, 2021). sRAGEs are generated through proteolysis of the extracellular domain of RAGE or through alternative RNA splicing (Sterenczak et al, 2009;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%